Digital Tools In The Development of Learning Sessions At The Basic And University Level In Lima - Hugo GONZÁLEZ; Patricia Zelaya (Communications of International Proceedings, 2022)
This research work analyzes the perceptions of 23 teachers between basic education (eleven) and university (twelve) about the use of technological tools in the development of the teaching-learning process through the moments of beginning, development and closing. It is concluded that teachers use certain tools such as Kahoot, Nearpord, Canva, Idukay, Mentimeter and YouTube to arouse student interest, make reflections or comments, promote critical thinking and reinforce student learning with the purpose of consolidating the processing knowledge or achieve significant learning.
Keywords: ICT; motivation; teaching-learning; feedback; critical thinking; meaningful learning.